Efeito cardioprotetor do d-limoneno sobre o infarto agudo do miocárdio em modelo animal - Durço, Aimée Obolari (2019)
Acute myocardial infarction (MI) presents a high mortality rate and its approach - pharmacological or percutaneous - does not significantly inhibit the ischemia / reperfusion (RI) damage caused, among others, by the increase of oxidative stress. The therapeutic properties of monoterpenes are already known and studies have shown that d-limonene - the most common natural monoterpene in nature, has antioxidant capacity and hypotensive action on blood pressure. Thus, the project sought to evaluate the cardioprotective effect of d-limonene on the IM model in the heart of Swiss mice. The animals were divided into 4 groups: control (vehicle - saline 0.9% + DMSO 0.1%), myocardial infarction (vehicle + 150mg / kg isoproterenol), d - limonene - DL 10μM d-limonene) and IM + DL (vehicle + isoproterenol + d-limonene) - the drugs were administered intraperitoneally, in two separate doses over a 24 hours interval. In the IM + DL group, d-limonene was administered 30 minutes after isoproterenol administration. Thus, subdermal electrodes were used to characterize the effect of d-limonene on electrocardiographic alterations; investigation of the effects of d-limonene on the infarct area by TTC labeling; histological changes by hematoxylin/eosin staining method (H & E); production of EROs by fluorescence with DHE; evaluation of the response of d-limonene to the antioxidant enzymes SOD and CAT its antioxidant capacity (FRAP) and action on the anti and pro-apoptotic proteins by immunofluorescence and Western Blotting techniques. Values of probability of p <0.05 were considered statistically significant. All data were expressed as mean ± Standard Mean Error (SEM), and the number of animals 5-6 per group. The results showed that d-limonene prevented ST segment elevation in 30% of the evaluated animals, prevented the increase of the QTc (71,66 ± 6,604 from 102,9 ± 5,04) and FC (332,7 ± 20,96 from 500,6 ± 13,69 bpm) interval, reduced the infarct area to 8.34%, and prevented histological changes in muscle fibers as well as decreased mononuclear cell infiltration, decreased oxidative stress by decreasing the ROS, restoring the SOD activity to values close to the control (24.35 ± 3.87 U/mg), to decrease the sulfidrylation, carbonylation and lipid peroxidation, and suppressed proapoptotic by reducing the expression of Bax and the activation of pro-caspase 3 to parameters equal to the control (93,54 ± 3,15 e 100 ± 2,37, respectively). Thus, the pharmacological findings of d-limonene converge to decrease the pro-apoptotic effect by reducing pro-apoptotic enzymes, reducing the infarct area, and producing ROS and increasing SOD activity.